Pengaruh Strategi Coping Terhadap Psychological Well Being Guru SD di Medan - Sipahutar, Arrhenius Stevan Bonari; Putri, Tika Kharisma; Naldi, Jefri Andri; Marpaung, Winida; Mirza, Rina (Jurnal Psikoedukasi dan Konseling, 2025)
Education is a learning effort with the aim of to improving the knowledge, abilities, attitudes and behavior of person or group with the notion of educating nation’s intelligence competence, which makes teachers the spearhead of education. The scope of this study intended to delve and investigate the relationship of coping strategies and psychological well-being, with a sample of 131 public elementary school teachers in the Medan Kota District, with coping strategies and psychological well-being scales consisting of 29 and 30 items respectively. The correlation method of linear regression analysis was used for data processing. The results showed a positive impact and significant relationship between problem-focused coping and psychological well-being with a value of β= 0.435 and a p value = 0.000 (0.00< 0.05). The findings of this research yielded a significant relationship within the guideline ending in a positive note regarding relationship between emotion-focused coping and psychological well-being with a value of β= 0.382 and p value = 0.000 (0.00<0.05). The effective contribution of coping strategies to psychological well-being was 59.1% and 40.9% were influenced by factors that were not studied.